Urban Sustainable Development Index: a geospatial approach to add Tree Cover to HDI in São Paulo City - Olivatto, Tatiane Ferreira; Di Lollo, José Augusto (Sociedade & Natureza, 2022)
Human Development Index (HDI) has become an important tool to measure the basics aspects of human quality of living, being based on educational, economic and longevity dimensions. Over the years, criticism about the absence of an environmental dimension has emerged together with the need for knowledge about sustainable development at a local scale. For these reasons, this paper proposes a new approach for HDI, the Urban Sustainable Development Index (USDI), adding a Tree Cover indicator based on the most accepted criteria of 30% of tree cover to provide high quality of life and kept the balance between the other three dimensions of HDI. The normalized and weighted proposed index showed to be a promising alternative to complement existing sustainable indices impractical at local scale, mainly because they are based on carbon emission measurements. A Tree Cover indicator is more comprehensive, assessing greenhouse gases sequestration, heat islands attenuation, flora preservation, sustenance of fauna habitat, mitigation of extreme weather events and maintenance of water resources and soil stability. The case study in São Paulo city indicated that the transition from HDI to USDI resulted in a negative variation of almost 0.12, mostly in city central regions, and an increase up to 0.08 in peripherical regions - revealing how powerful can be geospatial analysis at a local scale, considering that USDI differs from the spatial distribution of HDI, valuing the importance of a sustainable urban index.